Survival and Evaluation of Clinical and Laboratory Variables as Prognostic Indicators in Horses Hospitilized with Acute Diarrhea: 342 Cases (1995-2015) - Kovač Milomir (Sciendo, 2017)
A retrospective study was performed on 342 horses with acute diarrhea (equine colitis). Clinical and laboratory data were obtained upon arrival at the equine hospital. The main focus of this study was to find the difference between the clinical and laboratory variables of surviving and deceased acute colitis horses before the beginning of medical treatment, with the aim to provide a better guideline for determining the prognosis of survival. According to this retrospective study the lethality rate of acute equine colitis was 41.93 %. The time interval from the onset of acute diarrhea to the horse being taken to the clinic was significantly longer in the case of horses which had not survived. The heart rate, hematocrit, blood pH, blood hydrogen carbonate concentration, base excess and HCT/TPP ratio were shown to be significantly related to the survival of horses with colitis. Thus, the hematocrit, appeared to be the most relevant predictor of the outcome of acute equine colitis. Body temperature, respiration rate, total plasma protein and white blood cell count, did not show any prognostic significance.